FAKTOR RISIKO DIABETES MELITUS PADA USIA PRODUKTIF - Heru Purnomo; Hasriany Arifin; A. Suyatni Musrah; Putri Rahmah Alamsyah (Ensiklopedia of Journal, 2026)
Diabetes mellitus (DM) is a chronic and progressive noncommunicable disease that poses a public health problem in many countries. It is often referred to as a “silent killer” because the disease progresses slowly and often does not present with specific symptoms in its early stages. The objective of this study was to identify risk factors for diabetes mellitus among individuals of working age. A case-control study design was used. The study was conducted at the Tawaeli Community Health Center in September 2026. The study sample consisted of 20 cases and 20 controls. Purposive sampling was used. A research questionnaire was used as the data collection instrument. Data analysis was performed using univariate and bivariate methods. The results showed an association between dietary patterns (p-value: 0.025) and no association between the habit of drinking coffee or tea (p-value: 0.057) and the incidence of diabetes mellitus among individuals of working age. It is recommended that patients with type II diabetes mellitus control their body weight, manage their diet, engage in regular physical activity, and monitor their blood sugar levels to minimize the risk of type II diabetes.Keywords: Diabetes Mellitus, Coffee Consumption Habits, Dietary Patterns